Perilaku Pemilih dalam Pemilihan Kepala Daerah di Kota Banjar - Rizky Assodik; Regi Refian Garis; Ii Sujai (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by several factors that cause voter behavior in the regional head election in Banjar City. The purpose of this study is to determine voter behavior in the Regional Head Election in Banjar City. The method used in this study is descriptive analysis. There are 7 informants. Data collection techniques are literature studies, field studies (observations and interviews) and documentation. The author uses qualitative data analysis techniques through data processing from interviews and observations to draw conclusions so that they can answer the problems in the study. Based on the results of the study, it is known that: voter behavior in Banjar City is still dominated by the tendency of traditional voters and skeptical voters. This is evidenced by the problem of many voters who determine their choices based on following suit if most of their environment chooses a candidate pair, in addition, voters in determining their political choices are based on information obtained from their parents or from their environment, there are voters who are reluctant and lazy to pay attention to political contestation. There are obstacles to voter behavior in the regional head election in Banjar City, including unequal access to information so that people only get political information from unverified social media. In addition, the practice of money politics is still a reality that is difficult to avoid, where direct assistance or certain promises are the main considerations in choosing candidate pairs as well as past experiences. To overcome various obstacles, a number of efforts have been made, including the Banjar City General Election Commission (KPU) implementing a voter education program through direct outreach to the community, especially in villages and densely populated areas.